2023
DOI: 10.1177/15533506221150127
|View full text |Cite
|
Sign up to set email alerts
|

Towards Truly “Bespoke” Robotic Surgery: Vessel-Sparing Sigmoidectomy

Abstract: The proposed video-vignette represents a later step towards a truly robotically surgical approach, that combines oncological radicality and preservation of optimal blood flow during a sigmoidectomy for cancer. This totally robotic vessel-sparing approach doesn’t result in longer operative times, higher blood loss or extended length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, in our experience, the robot had an obvious advantage over the laparoscope when sewing the anastomotic stoma. During the surgery, the anastomotic wall was shaped by full thickness single-layer continuous suture ( 32 ). Unlike the long rigid laparoscopic instruments, the robot was equipped with wristed instrumentation with seven degrees of freedom (DOFs).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our experience, the robot had an obvious advantage over the laparoscope when sewing the anastomotic stoma. During the surgery, the anastomotic wall was shaped by full thickness single-layer continuous suture ( 32 ). Unlike the long rigid laparoscopic instruments, the robot was equipped with wristed instrumentation with seven degrees of freedom (DOFs).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that low ligation of the inferior mesenteric artery during radical resection of rectal cancer seemed to be associated with a lower risk of anastomotic leakage and overall morbidity (34). At the same time, "Bespoke " robotic surgery maintains optimal blood flow by preserving blood vessels, thereby reducing the incidence of anastomotic leakage after left hemicolectomy (35). An effective intervention measure that can reduce the incidence will be highly beneficial in clinical practice.…”
Section: Discussionmentioning
confidence: 99%